Theoretical investigation on a series of phosphorescent heteroleptic cyclometalated iridium (III) complexes containing substituted 2-(3-sulfonylfluorophenyl)pyridine ligands. (2nd September 2019) - Han, Deming; Hao, Fengqi; Li, Jingmei; Zhao, Lihui
Abstract: By using the density functional theory/time-dependent density functional theory methods, the electronic structure and photophysical properties of five heteroleptic cyclometalated Ir(III) complexes have been studied. The lowest absorption wavelengths are located at 350 nm for 1, 352 nm for 2, 354 nm for 3, 400 nm for 4 and 352 nm for 5, respectively. The phosphorescence wavelength of complexes 1 –5 are localized at 445, 473, 474, 490 and 466 nm, respectively, simulated in CH2 Cl2 medium at CAM-B3LYP level. It is expected that the theoretical results could help the experimentalists in synthesizing new excellent emitters for organic light-emitting diodes.